Kesejahteraan dan Keadilan Ekonomi Dalam Al-Qur'an: Tinjauan Surah At-Taubah: 34 dan An-Nisa: 58 - Siti Nur'ain; Taufik Warman Mahfuzh; Syamhudian Noor (STAI Kuala Kapuas, 2025)
This article aims to find the concept of welfare and Islamic economic justice contained in the Qur'an Surah At-Taubah: 34 and An-Nisa: 58, a type of library research study with the thematic interpretation method (maudhu'i) which focuses on the concept of welfare and Islamic economic justice contained in the Qur'an Surah At-Taubah: 34 and An-Nisa. The data collection technique uses document studies, the book of Tafsir Jami' Al Bayan Fii Tafsiril Qur'an. The analysis of verse interpretation data is relevant to the concept of welfare and Islamic economic justice. The basic principles of the Islamic economic system emphasize justice, trust, and social responsibility. Surah At-Taubah: 34 emphasizes the importance of spending wealth for the benefit of society, not just hoarding wealth without being distributed for social good. Meanwhile, Surah An-Nisa: 58 reminds of the importance of trust and justice in establishing laws and managing the economy.